Potential benefit of lymph node dissection during radical nephrectomy for kidney cancer: A review and critical analysis of current literature - Michele Marchioni; Daniele Amparore; Igino Andrea Magli; Riccardo Bertolo; Umberto Carbonara; Selcuk Erdem; Alexandre Ingels; Constantijn H.J. Muselaers; Onder Kara; Marco Mascitti; Tobias Klatte; Maximilian Kriegmair; et al. (Asian Journal of Urology)
Objective: The role of lymph node dissection (LND) is still controversial in patients with renal cell carcinoma undergoing surgery. We aimed to provide a comprehensive review of the literature about the effect of LND on survival, prognosis, surgical outcomes, as well as patient selection and available LND templates. Methods: Recent literature (from January 2011 to December 2021) was assessed through PubMed and MEDLINE databases. A narrative review of most relevant articles was provided. Results: The frequencies in which LNDs are being carried out are decreasing due to an increase in minimally invasive and nephron sparing surgery. Moreover, randomized clinical trials and meta-analyses failed to show any survival advantage of LND versus no LND. However, retrospective studies suggest a survival benefit of LND in high-risk patients (bulky tumors, T3-4 stage, and cN1 patients). Moreover, extended LND might provide important staging information, which could be of interest for adjuvant treatment planning. Conclusion: No level 1 evidence of any survival advantage deriving from LND is currently available in literature. Thus, the role of LND is limited to staging purposes. However, low grade evidence suggests a possible role of LND in high-risk patients. Randomized clinical trials are warranted to corroborate these findings.